Comparative Approaches to Energy Transition: Policy Guideline for Enhancing Thailand’s Path to a Low-Carbon Economy - Kamonphorn Kanchana (Energies)
Thailand’s transition to a low-carbon economy faces significant challenges, including a dependency on fossil fuels, fluctuating energy costs, and limited policy clarity. This study conducts a comparative analysis of energy transition policies in Germany, Japan, Australia, Malaysia, and Singapore to derive actionable lessons that can be adapted to Thailand’s socio-economic and energy contexts. Using the Integrated National Energy Planning (INEP) framework and Network Governance Theory, the research identifies key strategies, such as setting clear and achievable renewable energy targets, establishing robust legal frameworks, fostering multi-stakeholder engagement, and encouraging decentralized governance. The findings highlight the importance of long-term vision, inclusive governance, and targeted investments in renewable technologies to accelerate energy transitions. This paper presents policy guidelines to enhance Thailand’s energy security and contribute to its climate goals by promoting public awareness and strengthening institutional capacities. By adapting these strategies, Thailand can align with global energy trends, reduce its reliance on fossil fuels, and advance toward a resilient and sustainable energy system, aligned with global energy trends while addressing its unique socio-economic context.